Measurement Issues of Income and Non-Income Welfare Indicators: Assessment of Pakistan’s Pro-Poor Growth - Zaman, Khalid (International Journal of Economics and Financial Issues, 2015)
The major contribution of this study is to access number of income and non-income welfare indicators i.e., human development indicators (comprises primary school enrollment, secondary school enrollment, education expenditures, literacy rate, life expectancy, population per bed doctors, maternal and child health center, health expenditures, population planning, social security welfare and natural calamities); rural development measures (includes irrigation, land reclamation, rural development and rural electrification); safety net measures (contains food subsidy, food support programme, Tawwana Pakistan and low cost housing); and market access & community services measures (i.e., roads, buildings & highways and water supply and sanitation) for pro-poor growth reforms in Pakistan. The study covers the four most promising household income surveys of Pakistan i.e., 2002, 2006, 2008 and 2011. This study uses growth incidence curve (GIC) and non-income growth incidence curve (NIGIC) for measuring income and non-income indicators for Pakistan. The results more pronounced towards relative pro-poor growth in most of the non-income indicators, however, few non-income indicators favors absolute income of the poor in Pakistan. Keywords: Poverty; Growth; Inequality; Pro-poor growth; Non-income growth incidence curve; Pakistan. JEL Classifications: I32; O47